2015
DOI: 10.1111/irv.12308
|View full text |Cite
|
Sign up to set email alerts
|

Influenza seasonality in Madagascar: the mysterious African free‐runner

Abstract: BackgroundThe seasonal drivers of influenza activity remain debated in tropical settings where epidemics are not clearly phased. Antananarivo is a particularly interesting case study because it is in Madagascar, an island situated in the tropics and with quantifiable connectivity levels to other countries.ObjectivesWe aimed at disentangling the role of environmental forcing and population fluxes on influenza seasonality in Madagascar.MethodsWe compiled weekly counts of laboratory-confirmed influenza-positive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…Studies of influenza in the tropics started recently. We found reports for: Brazil [10, 11], Vietnam [12], Madagascar [13], Myanmar [14] and China [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Studies of influenza in the tropics started recently. We found reports for: Brazil [10, 11], Vietnam [12], Madagascar [13], Myanmar [14] and China [15]. …”
Section: Introductionmentioning
confidence: 99%
“…It will be interesting to learn whether these could be related to nonlinearities in the absolute humidity response, or whether these represent geographic cross-roads in areas of low seasonal forcing combined with robust coupling to regions subject to pure annual influenza cycles, aligned with winters in the northern (Northern China, Europe and North America) and southern hemispheres (Southern China, Australia). At the end of the spectrum of observed periodicities, a relatively remote subtropical island like Madagascar does not appear to experience influenza cycles entrained on any type of regular periodicity, based on analysis of long-term epidemiological records (19). Future analyses may shed light on the complexity of the interplay among environmental factors, population coupling, and the occasional term-time forcing, in fine-tuning seasonality of epidemic and pandemic influenza globally.…”
mentioning
confidence: 99%
“…Our assessment may appear applicable only to Madagascar due to its erratic influenza viral circulation pattern . However, we found that low successful strain match between WHO's recommended vaccination compositions and circulating viruses is a constant, not an exception as based on a review of the data from studies that investigated the proportion of influenza strain matching and which took into account the timing of vaccine delivery .…”
Section: Discussionmentioning
confidence: 89%
“…Nasopharyngeal and/or throat swabs from patients with influenza‐like illness (ILI) (as defined by the evolving WHO case definition) are analysed as previously described . Between 2002 and 2014, 4413 influenza viruses circulating in Madagascar were detected (for more details, see Alonso et al and Table ). As part of the WHO Global Influenza Surveillance and Response System (GISRS), at least twice a year the NIC of Madagascar shares influenza virus isolates with the WHO Collaborative Centre (WHO CC) of London where genetic and antigenic characterizations (HI assays) are performed for the update to the influenza vaccine recommendations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation